STATE`S MORAL CRUSADE AGAINST BEDROOM: MISDEMEANOUR OF PROSTITUTION IN NEW PUBLIC ORDER AND PEACE ACT - Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
In this paper, the author investigates the new Public Order and Peace Act (Ser. ZoJRM) and the provisions on so-called morale misdemeanour contained therein. Of these provisions, the one he recognizes as the most revolutionary is that of a new instance of perpetration under the old misdemeanour of prostitution. With this novelty, the Act extends liability for the misdemeanour not only to th e prostitute, but also to the user of her services. The author first puts forward a general criticism to the criminal and misdemeanour laws when these attempt to turn morality into the object of protection, which already has a general place in science. Then he investigates what perception of morality is protected by this offence, concluding that it crosses over into the sphere in which the freedom of citizens must in no way be interfered with – the sphere of voluntary sexual intercourse of two persons. For this reason, the author, in somewhat humorous fashion, warns, through the paper’s title, that the state will have to undertake a moral crusade against bedroom if it wants to consistently enforce these provisions. Moreover, the author sheds light on the origin of this moral stance, finding its roots in the societies with dominant protestant religious ethics as the moral foundation, as well as on its genesis, seeing it in the rise in sexual morality standards that occurred in the developing industrial societies in the second half of the nineteenth century. The author concludes that to our society and our natural moral stance such foreign moral implants are unnecessary, particularly if one considers that it is precisely in the country of their origin, the US, that they have long been rejected and marked as symbols of repression and non-liberty.